Insemination at an appointed time after estrous synchronization in beef cattle - Morrison, D.G.; Kiracofe, G.H.; Heersche, G. Jr.; Schalles, R.R.; McKee, M. (Kansas State University. Agricultural Experiment Station, 2011)
Eighty-three cows were each treated with a nine-day Syncro-mate B ear implant and one estrogen and progesterone injection. After implant removal, cows were artificially inseminated either 48, 54 or 60 hours later or 12 hours after estrus. An additional 16 cows received no treatment and were pasture mated. First service conception rates were 26.3, 23.8, 38.1, 33.3, and 68.8% for the 48-, 54-, and 60-post implant group, 12-hour post-estrus, and naturally bred cows, respectively.
Keywords: Beef; Insemination; Synchronization; Conception rates